UPDATE: METABOLIC DISORDERS OF PREECLAMPSIA A REVIEW - Dian Aprilia Damayanti; Mardiyono Mardiyono (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Preeclampsia is one of the contributors to the increased maternal morbidity and mortality rates in Indonesia. One of the disorders caused by the preeclampsia is metabolic disorders. The purpose of this study is to provide an overview of metabolic disorders that accompany preeclampsia.Methods: This was a literature review using electronic databases Science Direct and PubMed. Keywords used in searching literature were ‘preeclampsia’ and ‘metabolism disorder of preeclampsia’ with the year limit between 2010 and 2018. Articles published in English was chosen in this study.Results: The search found 3,823 articles, of which 14 articles were included in this study. Metabolic disorders that happened in the group of preeclampsia were higher RDW (Red blood cell distribution width), MTT (Biomarker), ADA (adenosine deaminase), CA-125 serum, triglycerides (TG), Angiotensin, cytokinin, CEC (Circulating endothelial cells), lipoprotein and cholesterol. Meanwhile, studies also found that preeclampsia caused the lower selenium serum, aromatase, and thiol-disulphide in the body.Conclusion: Preeclampsia proved causing the disorders of metabolic, mostly in the form of inflammation, endothelial cell damage and oxidative stress. Potential targets are needed for treatment of metabolic disorders in preeclampsia group both medically and non-medically especially for the lipid levels in preeclampsia.